2011
DOI: 10.3113/fai.2011.1127
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Joint Arthroereisis in the Management of Pediatric Flexible Flatfoot: A Critical Review of the Literature

Abstract: Current evidence is limited to consecutive case series or ad hoc case reports. Limited evidence exists to suggest that devices may have a more complex mode of action than simple motion blocking or axis altering effects. The interplay between osseous alignment and dynamic stability within the foot may contribute to the effectiveness of this procedure. Although literature suggests patient satisfaction rates of between 79% to 100%, qualitative outcome data based on disease specific, validated outcome tools may im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 82 publications
(129 reference statements)
6
80
0
22
Order By: Relevance
“…Studies have demonstrated increased ankle dorsiflexion, decreased foot pain, improvement of radiographic features, and even improvement in foot printing after this procedure. [56][57][58][59] A recent case series has also demonstrated the potential for maintenance of the foot in a corrected position even after subsequent implant removal. 60 One of the main concerns regarding this procedure is its high reported complication rate in 4% to 18% of cases in a recent literature review.…”
Section: Symptomatic Flatfootmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated increased ankle dorsiflexion, decreased foot pain, improvement of radiographic features, and even improvement in foot printing after this procedure. [56][57][58][59] A recent case series has also demonstrated the potential for maintenance of the foot in a corrected position even after subsequent implant removal. 60 One of the main concerns regarding this procedure is its high reported complication rate in 4% to 18% of cases in a recent literature review.…”
Section: Symptomatic Flatfootmentioning
confidence: 99%
“…60 One of the main concerns regarding this procedure is its high reported complication rate in 4% to 18% of cases in a recent literature review. 57 Frequently reported complications include malpositioning of the implant, improper correction of the deformity, extrusion of the implant from the sinus tarsi, foreign body reaction to the implant, peroneal spasm, and persistent foot pain. These complications are generally managed by implant removal.…”
Section: Symptomatic Flatfootmentioning
confidence: 99%
“…Arthroereisis (derived from Greek arthro - meaning joint and ereisis meaning lifting up ) is a procedure in which an implant screw is inserted between the posterior and anterior subtalar joints inside the sinus tarsi. The implantation of the screw expands the subtalar joint vertically, elevating the head of the talus which realigns the longitudinal arch of the foot and subsequently reduces the flatfoot deformity [7]. A number of implants have been used including bone, a polyethylene disk, silastic, a vitallium staple, and now more recently a titanium screw with soft-threaded design to resist extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…A number of implants have been used including bone, a polyethylene disk, silastic, a vitallium staple, and now more recently a titanium screw with soft-threaded design to resist extrusion. No bone drilling is necessary, and no cement is used, thus making arthroereisis a feasible minimally invasive procedure to treat symptomatic flatfoot [7].…”
Section: Introductionmentioning
confidence: 99%
“…Há duas revisões sistemáticas sobre o assunto, uma avalia a eficácia do tratamento conservador e a outra avalia os resultados da artrorrise subtalar 16,49 . …”
Section: Revisões Sistemáticas Préviasunclassified